if a=3 and b=-2 what is the value of the expression a-2 b-3
if a=3 and b=-2 what is the value of the expression a-2 b-3
IF your expression "a-2 b-3" is meant to be "(a-2)(b-3)" then Bill is correct, and the answer is -5 when a is 3 and b is -2.
However, if you mean"a - 2b -3" then, substituting the values you gave for a=3 and b=-2, that would be "3 - 2(-2) -3" which is the same as "3 +4 -3" and the expression evaluates to 4.
As in English, punctuation is very important in mathematical expressions: anything surrounded by parentheses must be evaluated first, to get a number, before any operators outside the parentheses are considered. Also note that the multiply (or divide) operators are "stronger" and must be evaluated before addition (or subtraction) are considered.
If your expression a-2 b-3 is the same as (a-2)(b-3), which is the same as (a-2) x (b-3):
(3-2)(-2-3) = (1)(-5) = -5 (negative 5)... do what is inside the parentheses first.